ANALYSIS OF THE EXPANSION OF THE PRINCIPLE OF LEGALITY IN RENEWING CRIMINAL LAW - Ahmad Arif Fadilah; Dwi Nur Fauziah Ahmad (Faculty of Law Atma Jaya Yogyakarta University, 2024)
The principle of legality is the most basic principle in the application of material criminal law. The principle of legality adhered to in Indonesian criminal law was originally the principle of formal legality. Meanwhile, in the renewal of criminal law embodied in the National Criminal Code, the principle of legality adopted also includes the principle of material legality. This article aims to analyze the expansion of the legality principle in the renewal of Indonesian criminal law and understand the meaning of the expansion of the legality principle. This article was written using a normative legal research method with a statutory approach. The result of this study is that the expansion of the legality principle in criminal law renewal is an effort to balance the fulfillment of legal objectives between legal certainty in the formal legality principle and justice in the material legality principle.